Diffusion-assisted post-crosslinking of polymer microspheres containing epoxy functional groups. (20th December 2017) - Oh, Joon-Suk; Kim, Minsoo P.; Kim, Joo-Hyung; Son, Hyunjong; Kim, Kyung-Heum; Kim, Sang-Hoon; Yoo, Ji-Beom; Lee, Youngkwan; Yi, Gi-Ra; Nam, Jae-Do
Abstract: With a diffusion-assisted post-crosslinking method, polymer microspheres containing epoxy groups are crosslinked with ethylenediamine (EDA), gradually diffusing and reacting in the particles via amine/epoxy ring-opening reactions as confirmed by FT-IR and DSC results. Using a microcompression test, we find that the mechanical property (deformability under different applied force, breaking points, and recoverability) of the crosslinked microspheres is varied when different amounts of EDA are used in the system, resulting from different crosslinking density of the particles. An additional feature of the EDA treatment is to generate amine groups on the surface of the microspheres, enabling us to produce hybrid microspheres. We exploit them as immobilization sites for gold nanoparticles, forming gold-coated crosslinked microspheres. We also introduce a sequential functionalization method to fabricate crosslinked microspheres with selective functional groups on the surface. This approach can be a facile method to produce functional microspheres with controlled mechanical and surface properties. Graphical abstract: Highlights: A synchronous crosslinking and amine-functionalization method for the polymer microsphere is introduced. The method allows us to readily adjust the mechanical property of polymer particles. Free amine functional groups on the surface of the microspheres can immobilize Au NPs. A sequential functionalization method is introduced to selectively functionalize the surface and to crosslink the interior.